SUMBANGAN ILMU PENUNJANG OLAHRAGA TERHADAP PEMBINAAN OLAHRAGA PRESTASI - Danang Wicaksono (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2016)
Performance in sports is something that is coveted by an athlete and coach. Sporting achievements obtained with a business is not easy. Science support is widely used in the implementation practice training process, in order to achieve performance in sports. Disciplines that support the achievement as sports medicine, sports biomechanics, sport psychology, sport pedagogy, sport sociology, sport history, sport philosophy. Seventh supporting science will provide support for the achievement of the sport through the process of training practice. Keywords: sports medicine, sports biomechanics, sport psychology, sport pedagogy, sport sociology, sport history, sport philosophy